Reading Park as a Learning Workshop - Fitri Dian Perwitasari; Dein Iftitah; Dian Novianti; Mus Nilamcaya (Ann Publisher, 2024)
Reading park is one of the educational programs organized to increase interest in reading and learning for the community. The place for carrying out community service activities is in Cikeusal village, Cirebo Regency which is held for a whole month from August 6, 2017 – September 6, 2017. The solutions offered are: 1. The absence of a village library, 2. Children's interest in reading is still low, 3. There are still elementary school children who cannot calistung, 4. Lack of interest in learning in children. Target of community service activities: 1. as a means of learning and reading for village children, 2. Interest in reading and learning in children increases, 3. Increase creativity. The KKM group 19 activity program—reading garden with the concept of a learning workshop went well and smoothly. KKM participants of Cirebon 7 Muhammadiyah University attracted the attention of the community by carrying out various activities both in groups and individuals. Community service in various aspects includes the role of the entire community. This activity provides an opportunity for students to share their knowledge with the community and allows them to use what they learn during their studies to solve problems in the field.